2001
DOI: 10.4141/a00-095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding exogenous phytase to nutrient-reduced corn- and wheat-based diets on performance and egg quality of two strains of laying hens

Abstract: Scott, T. A., Kampen, R. and Silversides F. G. 2001. The effect of adding exogenous phytase to nutrient-reduced corn-and wheat-based diets on performance and egg quality of two strains of laying hens. Can. J. Anim. Sci. 81: 393-401. A laying trial was conducted in which ISA-Brown and ISA-White hens were fed diets based on corn or wheat that had been pelleted to eliminate endogenous phytase. Control diets were formulated to contain adequate levels of all nutrients. Nutrient-reduced diets were formulated to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In ISA Brown hens fed a maize-based diet with P and Ca at 6.4 and 40.2 g-kg 1 (without exogenous phytase), the retention of P and Ca was 43.8 and 66.7%, respectively. The corresponding P and Ca retention values in hens fed a wheat-based diet were 39.2 and 62.8% (Scott et al, 2001). In both of the digestibility trials performed in the current study, the intestinal retention of P was significantly higher than the total tract retention.…”
Section: Discussionmentioning
confidence: 67%
“…In ISA Brown hens fed a maize-based diet with P and Ca at 6.4 and 40.2 g-kg 1 (without exogenous phytase), the retention of P and Ca was 43.8 and 66.7%, respectively. The corresponding P and Ca retention values in hens fed a wheat-based diet were 39.2 and 62.8% (Scott et al, 2001). In both of the digestibility trials performed in the current study, the intestinal retention of P was significantly higher than the total tract retention.…”
Section: Discussionmentioning
confidence: 67%
“…The effect of enzymes supplementation on egg weight was due to a difference in Haugh unit rather than shell or yolk weight. Scott et al (2001) also found that phytase increased albumen height (one parameter for determination of Haugh unit) in corn-based diet; the factors contributing to albumen height are not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…The use of phytase may release these essential nutrients thereby improving nutritional value of poultry diet, which resulted positively on productive performance of laying hens (Panda et al 2005). The response to the enzyme is not straightforward since it is relatively variable, depending upon factors such as bird age and type (Scott et al 2001), cereal grains, level and geographical locations (Chesson 2001), enzyme inclusion level (Karimi et al 2000) and feed processing (Svihus et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Phytate binds nutrients in addition to P, and the addition of phytase to feed caused the release of these nutrients and allows their absorption by the bird. Nutrients affected by phytates include minerals and protein (Ravindran et al, 1995;Selle et al, 2000), and phytase had been shown to affect the release of energy (Scott et al, 2001).…”
Section: Resultsmentioning
confidence: 99%